Association between Maternal Parity and Utilization of PMTCT Services in HIV/AIDS Prevention at Biak Kota Primary Health Center (PT. LARPA JAYA PUBLISHER, 2025)
Human Immunodeficiency Virus (HIV) is the causative agent of Acquired Immunodeficiency Syndrome (AIDS) and can be transmitted from mother to child during pregnancy, childbirth, and breastfeeding. Utilization of Prevention of Mother-to-Child Transmission (PMTCT) services by pregnant women is a crucial strategy to prevent vertical transmission of HIV. This study aimed to analyze factors associated with the utilization of PMTCT services among pregnant women attending antenatal care at Biak Kota Primary Health Center, Biak Numfor Regency. This study employed an observational design with a cross-sectional approach. A total of 80 pregnant women who attended antenatal care at Biak Kota Primary Health Center were selected using purposive sampling. Data were collected using a structured questionnaire. Data analysis included univariate analysis, bivariate analysis using the Chi-square test, and multivariate analysis to identify the most influential factors related to PMTCT service utilization.The results showed that educational level was not significantly associated with PMTCT service utilization (p = 0.168). In contrast, parity was significantly associated with PMTCT utilization (p = 0.007). Exposure to PMTCT-related information was also significantly associated with PMTCT service utilization (p < 0.05). Meanwhile, waiting time for services showed no significant association with PMTCT utilization (p = 0.092). Multivariate analysis revealed that exposure to PMTCT information was the most dominant factor associated with PMTCT service utilization. In conclusion, increased exposure to PMTCT information is associated with higher utilization of PMTCT services among pregnant women. Adequate dissemination of information enhances pregnant women’s knowledge and awareness of the benefits of PMTCT as an effective strategy for preventing mother-to-child transmission of HIV.